Saltwater aquariums for dummies (For dummies, ,, 2002)
Description Not Provided

Dolphin tale (Warner Home Video, 2012)
Eleven-year-old Sawyer Nelson becomes fascinated by the efforts of a local aquarium to save a dolphin injured in a crab trap.

Dolphin tale 2 ([Publisher not identified], 2014)
Winter's surrogate mother, the very elderly dolphin Panama, has passed away, leaving Winter without the only poolmate she has ever known. However, the loss of Panama may have even greater repercussions for Winter, who, according to USDA regulations, cannot be housed alone, as dolphins' social behavior requires them to be paired with other dolphins. Time is running out to find a companion for her before the team at Clearwater loses their beloved Winter to another aquarium.

Aquariums: the complete guide to freshwater and saltwater aquariums (Firefly Books, 2005)
Presents tips for tropical freshwater fish owners, including information on aquariums, water management, aquarium plants, aquascaping, feeding, compatibility, maintenance, healthcare, and heating and lighting.
Aquarium fish and plants , How fish live , The external anatomy , The internal anatomy , Behavior , Feeding , Healthcare in the aquarium , Freshwater fish , Labyrinth fish , The labyrinth fish aquarium , The Asian aquarium , Characins , The Amazon aquarium , A Central American cichlid aquarium , Cichlids , An aquarium for discus enthusiasts , A South American cichlid aquarium , Lake Malawi cichlids , A Lake Malawi cichlid aquarium , Lake Tanganyika cichlids , A Lake Tanganyika cichlid aquarium , An aquarium for other cichlid species , Loaches , Cyprinids , An aquarium for coldwater fish , An African aquarium , Killifish , A killifish aquarium , Rainbowfish , An aquarium of curiosities , Catfish , An oddballs aquarium , An aquarium of "useful" animals , A freshwater invertebrate aquarium , Livebearers , A Central American aquarium , A brackish-water aquarium., Breeding freshwater fish , The breeding tank , Water quality , Breeding stock , Raising the fry , Breeding cyprinids , Breeding characins , Breeding livebearers , Breeding labyrinth fish , Breeding catfish , Breeding killifish , Breeding cichlids , Saltwater fish , Damselfish and clownfish , A clownfish aquarium , Angelfish , Butterflyfish , Groupers and basslets , Wrasses , Lionfish , Tangs , Triggerfish , Boxfish, cowfish and porcupinefish , Blennies and gobies , Reef invertebrates aquarium , Miscellaneous species , Saltwater invertebrates aquarium , Aquarium plants , The biology of aquarium plants , The substrate , Aquarium lighting , Choosing and using plants , Feeding and propagating plants , A Dutch aquarium , Background plants , Midground plants , Foreground plants , Floating plants , Specimen plants., Setting up an aquarium , Water , The water cycle , Nitrogenous substances , Filtration , The natural habits of aquarium fish , Installing an aquarium , Choosing an aquarium , Positioning the aquarium , The aquarium in the home , The backdrop , The freshwater substrate , Aquarium kits , Heating for the freshwater aquarium , Filtration for the freshwater aquarium , Wooden decor for the freshwater aquarium , Rocky decor for the freshwater aquarium , Getting the freshwater system up and running , Introducing fish into a freshwater aquarium , Adding the fish , Maintaining a freshwater aquarium , Equipment for a saltwater aquarium , Maintaining a saltwater aquarium , Introducing fish into a saltwater aquarium.